Analyses of Requirements Established to Be Used for Design of a Test Workplace for Simulation of The Space Environment - Josef DVORAK (Communications of International Proceedings, 2024)
In this paper the author presents a part of results of the student teams projects elaborating the same assignment from industrial partner. The goal of the project was to design a workplace for testing parts for space (a modular vacuum chamber for simulating the space environment, a thermal unit including control with the help of a display and a pumping system including control) including handling of tested parts, testing progress, material flows, storage before and after testing, processing of test results etc. Part of the project is to design a suitable workplace configuration with regard to production costs, production difficulty, product quality and service life, work safety, ease of use, etc. A design study (visualization of the workplace), construction study and price balance were prepared for the system. It also includes a marketing market strategy. Design of the entire functional system was designed to meet all specified requirements.
Keywords: assigned; space; specification; teams; competition